Cold-Active Pectinolytic Activity Produced by Filamentous Fungi Associated with Antarctic Marine Sponges - Levican-Jaque, G; Chavez-Rosales, R; Gil-Duran, C (BioMed Central Ltd., 2018)
Background: Pectinase enzymes catalyze the breakdown of pectin, a key component of the plant cell wall. At industrial level, pectinases are used in diverse applications, especially in food-processing industry. Currently, most of the industrial pectinases have optimal activity at mesophilic temperatures. On the contrary, very little is known about the pectinolytic activities from organisms from cold climates such as Antarctica. In this work, 27 filamentous fungi isolated from marine sponges collected in King George Island, Antarctica, were screened as new source of cold-active pectinases. Results: In semi-quantitative plate assays, 8 out 27 of these isolates showed pectinolytic activities at 15 °C and one of them, Geomyces sp. strain F09-T3-2, showed the highest production of pectinases in liquid medium containing pectin as sole carbon source. More interesting, Geomyces sp. F09-T3-2 showed optimal pectinolytic activity at 30 °C, 10 °C under the temperature of currently available commercial mesophilic pectinases. Conclusion: Filamentous fungi associated with Antarctic marine sponges are a promising source of pectinolytic activity. In particular, pectinases from Geomyces sp. F09-T3-2 may be potentially suitable for biotechnological applica- tions needing cold-active pectinases. To the best of our knowledge, this is the first report describing the production of pectinolytic activity from filamentous fungi from any environment in Antarctica. © The Author(s) 2018.